ANTIOXIDANT ENZYMES ACTIVITY IN EXPERIMENTAL ISCHEMIA-REPERFUSION INJURY - Volotovska, N. V.; Kashchak, T. V. (International Journal of Medicine and Medical Research, 2019)
Background. Blood loss during civil and military limb trauma is the most common cause of preventable death. Complications due to the use of a hemostatic tourniquet are widely investigated nowadays. Therefore, the standards of the past have to be improved. Objective. The aim of the research is to study the reaction of the enzyme chain of the liver antioxidant system in the presence of modifications of ischemia-reperfusion injury (IRI). Methods. 210 white male-rats, aged 5-5.5 months, were used in the research. The dynamics of antioxidant enzymes activity catalase (Cat) and superoxide dismutase (SOD) in liver tissue in cases of modifications of ischemia-reperfusion injury (IRI) were studied. The period of investigation was in 24 hours, 3, 7, 14 days after the injury. Results. In cases of simulated IRI the catalase level mainly decreased at each period of the experiment. The peak of SOD activity was evidenced on the 1st, 3rd or 7th days after the experimental IRI according to the degree of trauma severity. Thus, IRI combined with severe blood loss and mechanical trauma caused the severest affection of the antioxidant system. Even a single application of hemostatic tourniquet caused similar wavelike reactions at different times. Conclusions. The development of IRI is accompanied by a significant depression of the liver antioxidant system. The most significant changes were evidenced in cases of IRI combined with blood loss and mechanical trauma, but even a single application of a tourniquet caused active response of the antioxidant enzymes.